Listening to difference: the construction of intersectional identity in VALORANT's sound design - Adams, Tate, author; Parks, Elizabeth S., advisor; Johnson Schroeder, Morgan K., committee member; Elkins, Evan, committee member; Martey, Rosa Mikeal, committee member (Colorado State University. Libraries, 2022)
As sound studies begins to interface more prominently with communication studies, the majority of research concerns rhetorical implications of vocality and sound's potential for argumentation and advocacy. This thesis contributes towards a growing body of research that identifies sound's influence in shaping our understandings of intersectional identity by providing several examples of how analyzing mediated sound design can uncover latent discourses of cultural difference. By combining communication studies, game studies, and sound studies it begins to establish a lexicon for discussing otherwise ineffable forms of representation in immersive and interactive media. This thesis sets out to answer two main research questions (RQs). RQ1 questions "How is player identity constructed in VALORANT through its voice communication affordances?" while RQ2 interrogates "How is intersectional identity communicated through VALORANT's sound design?" The three content chapters work in tandem to answer these research questions, and then reflect on what those answers mean for VALORANT players and audiences, scholars of games and sound, and the field of communication. This research is useful to VALORANT's player base and the widespread audience it commands insofar as it calls to the forefront the discourses of cultural difference which undergird the game's virtual acoustic design and sound affordances. Understanding that scholars of media, cultural studies, and communication overlap with gaming audiences, I am also optimistic that this thesis will inspire further work around sound design's potential for communicating discourses of cultural difference. For game studies scholars, this work encourages a dedicated practice of listening to and for discourse of cultural difference in games. Sound is an often-underserved element of games in critical scholarship, and (responding to RQ2) this thesis demonstrates how much hidden meaning is embedded in the subtle details of developer's sound design choices. This study contributes to game studies scholarship by excavating the potential of virtual acoustic to represent cultural difference. Specifically, Chapters 2 and 3 demonstrate how virtual acoustic design is used to immerse players and characters within a particular diegetic context (space, place, time) in digital environments. Further, Chapter 3 also brings into focus the politics and economics of representation entailed in cosmetic accessorizing in online gaming. For scholars of sound, this thesis exemplifies the importance of developing critical tools for understanding how audio cues are used in mediated sound design to communicate notions of intersectional identity. As a rapidly growing interdisciplinary field, sound studies scholars could contribute a great deal of knowledge towards the different ways in which representations are codified in industrial practices. When communication studies turns its attention toward mediated sound design it is especially well-oriented to understand and critique the influence of virtual acoustic design on our conception of social reality. This study emphasizes the possibilities for rhetorical scholarship to critically assess forms of representation that are otherwise quite difficult to put words to. This thesis also exemplifies the potential of adopting vibration as a central organizing metaphor for communication theory. An acoustic approach to orientation in Chapter 2 conceptualizes sound design as innately rhetorical, and often strategic. A vibrational reading of stereotype in Chapter 3 which emphasizes the ephemeral, dynamic, and immersive nature of representation. A resonant approach to access and advocacy in Chapter 1 uses the metaphor of apprehending vibration to highlight the importance of feeling heard in relation to representation, safety, and community.
Keywords: game studies; sound; virtual acoustic design; new media; controlling sounds; stereotypes